Teachers in Charter and Traditional Schools - Bomotti, Sally; Ginsberg, Rick; Cobb, Brian (Education Policy Analysis Archives, 1999)
Teachers from charter and traditional schools in Colorado were queried about their perceptions of their level of empowerment, school climate, and working conditions. Using a cluster sampling design, approximately 100 teachers from 16 charter schools and 100 teachers from seven traditional schools were surveyed by combining several well-established instruments to measure empowerment, school climate, and working conditions. Factor analyses yielded three composite variables each for the three constructs. One-way analyses of variance were used to explore these teachers' differences in perceptions. Results yielded consistent and practically significant differences in these charter and traditional school perceptions of empowerment, school climate, and working conditions. Not all of these differences, however, were consistent with expectations given the educational and legislative contexts driving Colorado's charter school movement. Implications and recommendations for future research are given.